Studi Geologi Lingkungan Berbasis Kearifan Lokal Pada Objek Wisata Candi Tebing Gunung Kawi, Tampaksiring - I Kadek Adiana Putra; Wayan Sauri Peradhayana; Gede Surya Mahendra (Program Studi Teknik Lingkungan Unmas Denpasar, 2021)
The objectives of tourism development are to introduce, utilize, protect and improve the quality and attractiveness of tourism, maintain Balinese environmental protection norms, religious values, culture and natural life, prevent negative impacts caused by tourism activities, and improve the welfare of the community. The tourist attraction of the Candi Tebing Gunung Kawi is a sacred area located in the Banjar Penaka, Tampaksiring District, in Gianyar Regency. The results of preliminary observations on geological traces in both places show the unique formation, stratigraphy, and rock-forming minerals to be revealed either from the volcanic activity of Mount Batur and also influenced by tectonic activity that had taken place at that time. The results of this study indicate that the rock stratigraphy at the Candi Tebing Gunung Kawi tourist attraction belongs to the principle of lateral sustainability. The role of geotourism looks very significant in revealing the role of geology in tourism development, especially in the Pura Gunung Kawi. Local wisdom that is used is to prohibit tourists who are on their period from entering tourism sites, and conducting searches with the aim of cleaning the temple in a nocturnal manner which is carried out every piodalan, puja wali or caru manca kelud every 10 years.